2012
DOI: 10.2337/dc11-1597
|View full text |Cite
|
Sign up to set email alerts
|

Integrating an Automated Diabetes Management System Into the Family Management of Children With Type 1 Diabetes

Abstract: OBJECTIVEThe study objective was to evaluate how the use of a pervasive blood glucose monitoring (BGM) technology relates to glycemic control, report of self-care behavior, and emotional response to BGM of children with type 1 diabetes and their parents.RESEARCH DESIGN AND METHODSForty-eight children aged less than 12 years (mean 8.8 years) with type 1 diabetes were randomly assigned to one of two study groups, a control group (conventional care without technology) or an experimental group (conventional care w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…the comparison of results from the ADMS, 23 the Diabeo system, 26 applications of the pioneering system of Albisser et al 16 and the implementation of the TeleMed system 21 the results from the classical way of teletransmitting data, which are characterized by a not-so-frequent assessment of the available patient data and which bring one closer to the usual care systems it is possible to draw the conclusion that the real-time monitoring of the patient's state connected with an automatic feedback messages sent to the patient can give a much better improvement than the classical telematic support. However, can we afford increasing frequency without changing the established model of diabetes treatment?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the comparison of results from the ADMS, 23 the Diabeo system, 26 applications of the pioneering system of Albisser et al 16 and the implementation of the TeleMed system 21 the results from the classical way of teletransmitting data, which are characterized by a not-so-frequent assessment of the available patient data and which bring one closer to the usual care systems it is possible to draw the conclusion that the real-time monitoring of the patient's state connected with an automatic feedback messages sent to the patient can give a much better improvement than the classical telematic support. However, can we afford increasing frequency without changing the established model of diabetes treatment?…”
Section: Discussionmentioning
confidence: 99%
“…It can be realized directly by the healthcare provider or by the automatic data analysis and decision support advisory systems. It was demonstrated in the Albisser et al, 16 TeleMed, 21 ADMS, 23 Diabeo, 26 and WellDoc 24,25 systems that both these solutions can be effective. In future, the automated systems should prevail in within-theday applications because the direct interaction with the healthcare provider is more expensive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study was not designed by the authors (see [18] for more details), it was completed after the interview study, enabling the themes identified to be explored in more detail, in particular, the changes in emotional response to BGM by the participants.…”
Section: Trial Of a New Pervasive Technologymentioning
confidence: 99%
“…Kasesniemi, 2003;Oksman and Rautiainen, 2003;Ito, 2005;Chen and Katz, 2009;Kaare et al, 2007;Plowman et al, 2010;Green et al, 2011Green et al, , 2012Green et al, , 2013Hertlein, 2012;Jackson et al, 2012;Palmer et al, 2012;Plowman and McPake, 2013;McPake et al, 2013;Livingstone et al, 2014b;Livingstone et al, 2015). Other studies address specific groups within these ages, such as children with diabetes (Hirose et al, 2012;Toscos et al, 2012), asthma (Mosnaim et al, 2012) intellectual and developmental disabilities (Palmer et al, 2012;Hwang et al 2014), complex communication needs (Light and McNaughton, 2012) and obesity (Woolford et al, 2012;Sharifi et al, 2013). In Europe, the most comprehensive studies have been produced by the EU projects, "EU Kids Online" 2 and "Net Children Go Mobile", 3 which conducted a panEuropean survey of interviews over 33,000 children (as well as some of their parents and teachers) between 2010-2014.…”
Section: Introductionmentioning
confidence: 99%